Direct evidence for functional TRPV1/TRPA1 heteromers - Fischer, Michael; Balasuriya, Dilshan; Jeggle, Pia; Goetze, Tom A.; Mcnaughton, Peter A.; Reeh, Peter; Edwardson, J. Michael (Pflügers Archiv: European Journal of Physiology, 2014)
Transient receptor potential cation channel, subfamily V, member 1 (TRPV1) plays a key role in sensing environmental hazards and in enhanced pain sensation following inflammation. A considerable proportion of TRPV1-expressing cells also express transient receptor potential cation channel, subfamily A, member 1 (TRPA1). There is evidence for a TRPV1-TRPA1 interaction that is predominantly calcium-dependent, and it has been suggested that the two proteins might form a heteromeric channel. Here, we constructed subunit concatemers to search for direct evidence for such an interaction. We found that a TRPV1::TRPV1 concatemer and TRPV1 formed channels with similar properties. A TRPV1::TRPA1 concatemer was responsive to TRPV1 agonists capsaicin, acidic pH and ethanol, but not to TRPA1 agonists. Isolated TRPV1 and TRPV1::TRPA1 imaged by atomic force microscopy (AFM) both had molecular volumes consistent with the formation of tetrameric channels. Antibodies decorated epitope tags on TRPV1 with a four-fold symmetry, as expected for a homotetramer. In contrast, pairs of antibodies decorated tags on TRPV1::TRPA1 predominantly at 180°, indicating the formation of a channel consisting of two TRPV1::TRPA1 concatemers arranged face to face. TRPV1::TRPA1 was sensitized by PKC activation and could be inhibited by a TRPV1 antagonist. TRPV1::TRPA1 was activated by heat and displayed a threshold and temperature coefficient similar to TRPV1. However, the channel formed by TRPV1::TRPA1 has only two binding sites for capsaicin and shows less total current and a smaller capsaicin-induced shift in voltage-dependent gating than TRPV1::TRPV1 or TRPV1. We conclude that the presence of TRPA1 exerts a functional inhibition on TRPV1.
EVALuna2:2456